Poly(lactide) and Ni nanoparticles supported thermally reduced graphene oxide nanoarchitecture for magnetic stimuli-responsive material - Nisar, Muhammad; Santos, Leonardo Moreira Dos; Ullah, Hameed [UNESP]; Galland, Griselda Barrera; Geshev, Julian; Bergmann, Carlos; Quijada, Raúl (Wiley, 2025)
In recent years, biodegradable plastics have gained significant attention as a strategy to reduce environmental contamination. However, achieving uniform dispersion of magnetic nanoparticles (MNPs) in polymers remains challenging due to magnetic aggregation. Core-shell encapsulation has emerged as an effective method to address this issue. In this study, nickel (Ni) nanoparticles (NPs) were supported on thermally reduced graphene oxide (TrGO), reduced at two distinct temperatures (600 and 1000°C), and used as nano-fillers to fabricate PLA nanocomposites. The mechanical, thermal, and magnetic properties of these composites were systematically investigated. X-ray diffraction (XRD) analysis displayed characteristic peaks for both graphene and Ni, with an estimated Ni NP size of 3.59 nm. Raman spectroscopy confirmed the D and G bands of graphene, along with distinct peaks of Ni. Surface area and elemental analyses indicated an increase in surface area and carbon content with thermal reduction, followed by a predictable decrease after supporting Ni NPs. Atomic absorption spectroscopy revealed that 8–12 wt.% of MNPs were successfully loaded onto the TrGO surface. Fourier transform infrared spectroscopy (FT-IR) demonstrated that the polymer's chemical structure remained unchanged after nanoparticle incorporation. Uniform dispersion of the filler was observed through fracture interface scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Thermogravimetric analysis (TGA) showed a slight improvement in the initial degradation temperature of the PLA nanocomposites upon NP addition, although the final thermal stability was lower compared to neat PLA. Differential scanning calorimetry (DSC) showed a small increase in crystallinity, while the melting temperature remained unchanged. The addition of the filler led to a slight improvement in the elastic modulus. The hydrophilic nature of the nanocomposites was confirmed by water contact angle measurements. Notably, the incorporation of TrGO-Ni nanoparticles converted the original diamagnetic PLA matrix into a ferromagnetic material. Highlights: Innovative magnetic polymer nanocomposites. Novel synthesis method for TrGO-supported nickel nanoparticles. Enhanced thermal stability is achieved by incorporating carbon-based filler. The mechanical properties of the composites were improved compared to neat PLA.
Keywords: biodegradable polymer; graphene oxide; magnetic properties; metal nanoparticles